Estudio de factibilidad para la creación de una empresa de transporte de containers en la ciudad de Quevedo, Año 2014. - Benavides Oñate, Jessica Alexandra (2015)
This research seeks to create a container transport company that generates the shuttle them between major cities of Ecuador and Canton Quevedo. The purpose is also to carry out the project is to offer a quality service, which xix show good management on containers, so it seeks to monitor them from their situational state thereof during the shifting of the burden, constantly reporting departure and delivery of the same. Container transport cargo focuses on export and import, of 40-20 feet. For this, there is the acquisition of a fleet of trucks and chassis and hiring professional drivers with type E license, they are trained in everything related to container and logistics to provide better service. In addition, the containers are tracked by a GPS satellite 24 hours, 365 days a year, so the customer will know where your container at any given time. Once cited some of the features offered by the project, which is looking to settle in the market showing a picture of a well established company which provides security to customers, the same that propose to solve their problems, so that meets one hundred percent their requirements.